Transcranial Magnetic Stimulation to Assess Exercise-Induced Neuroplasticity - Turco, Claudia V.; Nelson, Aimee J. (Frontiers in Neuroergonomics, 2021)
Aerobic exercise facilitates neuroplasticity and has been linked to improvements in cognitive and motor function. Transcranial magnetic stimulation (TMS) is a non-invasive technique that can be used to quantify changes in neurophysiology induced by exercise. The present review summarizes the single- and paired-pulse TMS paradigms that can be used to probe exercise-induced neuroplasticity, the optimal stimulation parameters and the current understanding of the neurophysiology underlying each paradigm. Further, this review amalgamates previous research exploring the modulation of these paradigms with exercise-induced neuroplasticity in healthy and clinical populations and highlights important considerations for future TMS-exercise research.